Complication of trans-rectal prostate biopsy based on Clavien index: 5 years of experience - Adhitya Fajar Prasetya; Johan Renaldo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Trans-rectal prostate biopsy has become the gold standard for early diagnosis of prostate cancer in developing countries. Despite its low risk, there are some post-procedural complications. The complications are classified by using a modified Clavien-Dindo system. The study aimed to recognize complications of trans-rectal prostate biopsy procedure by using Clavien-Dindo classification index. All patients undergoing trans-rectal prostate biopsy procedure in the Department of Urology, Dr. Soetomo General Hospital between January 2015-December 2019, were retrospectively analyzed in terms of post-procedural complaints, underlying comorbidities and ongoing additional examinations. The complaints were compiled into Clavien-Dindo classification. Univariate analysis of various predictors of post-procedural complications was also conducted. It was found 98 complication events from 400 patients (24.5%). Most complications were 1st degree (dysuria, hematuria, urinary retention, fever, rectal pain and bleeding, erectile dysfunction, and constipation).  In univariate analysis, positive results of urinary culture correlated to the emergence of post-procedural complications. In conclusion, the incidence of post-trans-rectal prostate biopsy complication in Dr. Soetomo General Hospital reached 24.5%. From all of the risk factors, positive urinary culture is related to the post-biopsy complication. Most complications are in the 1st grade of Clavien index, suggesting that the procedure is relatively safe and has a low risk